Wild about books - Sierra, Judy.; Brown, Marc Tolon (New York : Knopf, 2004)
A librarian named Molly McGrew introduces the animals in the zoo to the joy of reading when she drives her bookmobile to the zoo by mistake.
Keywords: Zoo animals -- Fiction; Books and reading -- Fiction; Bookmobiles -- Fiction; Libraries -- Fiction; Stories in rhyme